Development and integration of a wound cleansing pathway into clinical practice. (2nd November 2021) - Vernon, Tracy; Moore, Kelly; Collier, Mark
Abstract : Wound bed preparation has come into sharper focus over the past decade, with strategies identified to improve wound condition. This article focuses on implementing a wound cleansing policy and measuring, through audits, how this change affected rates of wound infection. From 2016 onwards, the Skin Integrity Team at Doncaster and Bassetlaw Teaching Hospitals NHS Foundation Trust took steps to revise and improve wound care practices. This resulted in the introduction of a wound cleansing pathway incorporating a surfactant-based cleanser in place of saline, with subsequent staff training and other changes made to practice. This study details the steps taken to implement the new pathway, which brought a reduction in wound infections of 84.3% between 2017 and 2019.